2022
DOI: 10.3389/fimmu.2022.895110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ferroptosis-Related Prognostic Signature and Subtypes Related to the Immune Microenvironment for Breast Cancer Patients Receiving Neoadjuvant Chemotherapy

Abstract: PurposeTo identify molecular clusters associated with ferroptosis and to develop a ferroptosis-related signature for providing novel potential targets for the recurrence-free survival and treatment of breast cancer.MethodsFerroptosis-related gene (FRG) signature was constructed by univariate and multivariate Cox regression and least absolute shrinkage and selection operator (LASSO). Receiver operating characteristic curves, Kaplan–Meier survival analysis, principal component analysis, and univariate and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In vivo , iron metabolism and homeostasis are linked with the TME, while ferroptosis plays an important role in tumor immunity ( Lu et al, 2021 ). In a previous study, 18 Ferroptosis-related genes (FRG) were used to divide breast cancer patients into three clusters to improve immunotherapy outcomes, and an immunomicroenvironment and therapeutic response can be prognostically predicted by the FRG signature ( Xu et al, 2022 ). Based on the hallmark gene sets, ATP6AP1 expression was positively associated only with the myogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , iron metabolism and homeostasis are linked with the TME, while ferroptosis plays an important role in tumor immunity ( Lu et al, 2021 ). In a previous study, 18 Ferroptosis-related genes (FRG) were used to divide breast cancer patients into three clusters to improve immunotherapy outcomes, and an immunomicroenvironment and therapeutic response can be prognostically predicted by the FRG signature ( Xu et al, 2022 ). Based on the hallmark gene sets, ATP6AP1 expression was positively associated only with the myogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (82) constructed a nomogram based on nine ferroptosis-related genes. These ferroptosis-related genes were significantly associated with the level of immune cell infiltration in patients with breast cancer, suggesting their potential use as therapeutic targets or biomarkers (82)(83)(84)(85)(86)(87)(88)(89)(90). Additionally, studies have shown that the deletion of CircRHOT1 inhibits breast cancer cell proliferation and induces apoptosis, while the knockdown of CLCA2, REEP6, SPDEF and CRAT can predict breast cancer prognosis based on metabolic gene classification (91,92).…”
Section: Ferroptosis and Breast Cancermentioning
confidence: 98%